Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the equation [tex]\(\sqrt{3 - 3x} = 3 + \sqrt{3x + 2}\)[/tex], we will follow these algebraic steps:
1. Isolate one of the square roots:
[tex]\[ \sqrt{3 - 3x} = 3 + \sqrt{3x + 2} \][/tex]
To isolate the square root on the left, we leave it as it is for now.
2. Square both sides to eliminate the square root:
[tex]\[ (\sqrt{3 - 3x})^2 = (3 + \sqrt{3x + 2})^2 \][/tex]
Simplifying both sides, we get:
[tex]\[ 3 - 3x = 9 + 6\sqrt{3x + 2} + (3x + 2) \][/tex]
3. Combine like terms:
[tex]\[ 3 - 3x = 9 + 6\sqrt{3x + 2} + 3x + 2 \][/tex]
Simplifying the right side further:
[tex]\[ 3 - 3x = 11 + 6\sqrt{3x + 2} + 3x \][/tex]
4. Isolate the term involving the square root:
[tex]\[ 3 - 3x - 11 - 3x = 6\sqrt{3x + 2} \][/tex]
Combine the constants and linear terms on the left:
[tex]\[ -8 - 6x = 6\sqrt{3x + 2} \][/tex]
5. Divide both sides by 6 to simplify:
[tex]\[ \frac{-8 - 6x}{6} = \sqrt{3x + 2} \][/tex]
Simplifying the left side:
[tex]\[ -\frac{4 + 3x}{3} = \sqrt{3x + 2} \][/tex]
6. Square both sides again to eliminate the remaining square root:
[tex]\[ \left(-\frac{4 + 3x}{3}\right)^2 = (3x + 2) \][/tex]
Simplify each side:
[tex]\[ \left(\frac{4 + 3x}{3}\right)^2 = 3x + 2 \][/tex]
Expanding the square on the left:
[tex]\[ \frac{(4 + 3x)^2}{9} = 3x + 2 \][/tex]
7. Clear the fraction by multiplying each term by 9:
[tex]\[ (4 + 3x)^2 = 9(3x + 2) \][/tex]
Expanding both sides:
[tex]\[ 16 + 24x + 9x^2 = 27x + 18 \][/tex]
8. Combine like terms and set the equation to zero:
[tex]\[ 9x^2 + 24x + 16 = 27x + 18 \][/tex]
Bring all the terms to one side:
[tex]\[ 9x^2 + 24x + 16 - 27x - 18 = 0 \][/tex]
Simplifying:
[tex]\[ 9x^2 - 3x - 2 = 0 \][/tex]
9. Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex] to solve for [tex]\(x\)[/tex]:
Here, [tex]\(a = 9\)[/tex], [tex]\(b = -3\)[/tex], and [tex]\(c = -2\)[/tex].
[tex]\[ x = \frac{-(-3) \pm \sqrt{(-3)^2 - 4(9)(-2)}}{2(9)} \][/tex]
Simplifying inside the square root:
[tex]\[ x = \frac{3 \pm \sqrt{9 + 72}}{18} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{81}}{18} \][/tex]
[tex]\[ x = \frac{3 \pm 9}{18} \][/tex]
Solving for the two cases:
[tex]\[ x = \frac{3 + 9}{18} = \frac{12}{18} = \frac{2}{3} \][/tex]
[tex]\[ x = \frac{3 - 9}{18} = \frac{-6}{18} = -\frac{1}{3} \][/tex]
10. Check both potential solutions in the original equation:
[tex]\[ \sqrt{3 - 3 \left( \frac{2}{3} \right)} = 3 + \sqrt{3 \left( \frac{2}{3} \right) + 2} \][/tex]
[tex]\[ \sqrt{3 - 2} = 3 + \sqrt{2 + 2} \][/tex]
[tex]\[ \sqrt{1} = 3 + \sqrt{4} \][/tex]
[tex]\[ 1 = 3 + 2 \][/tex]
This is not true, so [tex]\(x = \frac{2}{3}\)[/tex] is not a solution.
Similarly, for [tex]\(x = -\frac{1}{3}\)[/tex]:
[tex]\[ \sqrt{3 - 3 \left( -\frac{1}{3} \right)} = 3 + \sqrt{3 \left( -\frac{1}{3} \right) + 2} \][/tex]
[tex]\[ \sqrt{3 + 1} = 3 + \sqrt{-1 + 2} \][/tex]
[tex]\[ \sqrt{4} = 3 + \sqrt{1} \][/tex]
[tex]\[ 2 = 3 + 1 \][/tex]
This is also not true, so [tex]\(x = -\frac{1}{3}\)[/tex] is not a solution either.
Therefore, after thoroughly checking both potential solutions, we find that there are no valid solutions to the given equation. Thus, the solution set is empty.
[tex]\[ \boxed{\emptyset} \][/tex]
1. Isolate one of the square roots:
[tex]\[ \sqrt{3 - 3x} = 3 + \sqrt{3x + 2} \][/tex]
To isolate the square root on the left, we leave it as it is for now.
2. Square both sides to eliminate the square root:
[tex]\[ (\sqrt{3 - 3x})^2 = (3 + \sqrt{3x + 2})^2 \][/tex]
Simplifying both sides, we get:
[tex]\[ 3 - 3x = 9 + 6\sqrt{3x + 2} + (3x + 2) \][/tex]
3. Combine like terms:
[tex]\[ 3 - 3x = 9 + 6\sqrt{3x + 2} + 3x + 2 \][/tex]
Simplifying the right side further:
[tex]\[ 3 - 3x = 11 + 6\sqrt{3x + 2} + 3x \][/tex]
4. Isolate the term involving the square root:
[tex]\[ 3 - 3x - 11 - 3x = 6\sqrt{3x + 2} \][/tex]
Combine the constants and linear terms on the left:
[tex]\[ -8 - 6x = 6\sqrt{3x + 2} \][/tex]
5. Divide both sides by 6 to simplify:
[tex]\[ \frac{-8 - 6x}{6} = \sqrt{3x + 2} \][/tex]
Simplifying the left side:
[tex]\[ -\frac{4 + 3x}{3} = \sqrt{3x + 2} \][/tex]
6. Square both sides again to eliminate the remaining square root:
[tex]\[ \left(-\frac{4 + 3x}{3}\right)^2 = (3x + 2) \][/tex]
Simplify each side:
[tex]\[ \left(\frac{4 + 3x}{3}\right)^2 = 3x + 2 \][/tex]
Expanding the square on the left:
[tex]\[ \frac{(4 + 3x)^2}{9} = 3x + 2 \][/tex]
7. Clear the fraction by multiplying each term by 9:
[tex]\[ (4 + 3x)^2 = 9(3x + 2) \][/tex]
Expanding both sides:
[tex]\[ 16 + 24x + 9x^2 = 27x + 18 \][/tex]
8. Combine like terms and set the equation to zero:
[tex]\[ 9x^2 + 24x + 16 = 27x + 18 \][/tex]
Bring all the terms to one side:
[tex]\[ 9x^2 + 24x + 16 - 27x - 18 = 0 \][/tex]
Simplifying:
[tex]\[ 9x^2 - 3x - 2 = 0 \][/tex]
9. Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex] to solve for [tex]\(x\)[/tex]:
Here, [tex]\(a = 9\)[/tex], [tex]\(b = -3\)[/tex], and [tex]\(c = -2\)[/tex].
[tex]\[ x = \frac{-(-3) \pm \sqrt{(-3)^2 - 4(9)(-2)}}{2(9)} \][/tex]
Simplifying inside the square root:
[tex]\[ x = \frac{3 \pm \sqrt{9 + 72}}{18} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{81}}{18} \][/tex]
[tex]\[ x = \frac{3 \pm 9}{18} \][/tex]
Solving for the two cases:
[tex]\[ x = \frac{3 + 9}{18} = \frac{12}{18} = \frac{2}{3} \][/tex]
[tex]\[ x = \frac{3 - 9}{18} = \frac{-6}{18} = -\frac{1}{3} \][/tex]
10. Check both potential solutions in the original equation:
[tex]\[ \sqrt{3 - 3 \left( \frac{2}{3} \right)} = 3 + \sqrt{3 \left( \frac{2}{3} \right) + 2} \][/tex]
[tex]\[ \sqrt{3 - 2} = 3 + \sqrt{2 + 2} \][/tex]
[tex]\[ \sqrt{1} = 3 + \sqrt{4} \][/tex]
[tex]\[ 1 = 3 + 2 \][/tex]
This is not true, so [tex]\(x = \frac{2}{3}\)[/tex] is not a solution.
Similarly, for [tex]\(x = -\frac{1}{3}\)[/tex]:
[tex]\[ \sqrt{3 - 3 \left( -\frac{1}{3} \right)} = 3 + \sqrt{3 \left( -\frac{1}{3} \right) + 2} \][/tex]
[tex]\[ \sqrt{3 + 1} = 3 + \sqrt{-1 + 2} \][/tex]
[tex]\[ \sqrt{4} = 3 + \sqrt{1} \][/tex]
[tex]\[ 2 = 3 + 1 \][/tex]
This is also not true, so [tex]\(x = -\frac{1}{3}\)[/tex] is not a solution either.
Therefore, after thoroughly checking both potential solutions, we find that there are no valid solutions to the given equation. Thus, the solution set is empty.
[tex]\[ \boxed{\emptyset} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.